2021
DOI: 10.1136/bmjgh-2021-005847
|View full text |Cite
|
Sign up to set email alerts
|

Completeness and quality of low back pain prevalence data in the Global Burden of Disease Study 2017

Abstract: IntroductionCompleteness of Global Burden of Disease (GBD) Study data is acknowledged as a limitation. To date, no study has evaluated this issue for low back pain, a leading contributor to disease burden globally.MethodsWe retrieved reports, in any language, based on citation details from the GBD 2017 study website. Pairs of raters independently extracted the following data: number of prevalence reports tallied across countries, age groups, gender and years from 1987 to 2017. We also considered if studies enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 11 publications
(13 reference statements)
1
23
0
Order By: Relevance
“…Annual United States (US) all-payer combined NP and low back pain (LBP) costs are estimated to be $134.5 billion, making spinal disorders the costliest condition type, more than all other musculoskeletal conditions combined ($129.8 billion) and more than the cost of diabetes ($111.2 billion) 3 . NP estimated years lived with disability (YLD) is also high 1,4 , although YLD estimates may over or underrepresent actual NP disability [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Annual United States (US) all-payer combined NP and low back pain (LBP) costs are estimated to be $134.5 billion, making spinal disorders the costliest condition type, more than all other musculoskeletal conditions combined ($129.8 billion) and more than the cost of diabetes ($111.2 billion) 3 . NP estimated years lived with disability (YLD) is also high 1,4 , although YLD estimates may over or underrepresent actual NP disability [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jin et al 8 report the number of incident cases of LBP for 195 countries for 1990 and 2017, but GBD 2017 only includes 4 country-years of incidence data. Wu et al 6 reported that for the year 2017, there were marked differences in LBP point prevalence across global regions; yet, our review 7 found that none of the prevalence studies in GBD 2017 provide prevalence data for the year 2017. Studies from China 9 (including their 33 regions), Brazil 10 (including their 27 states) and Iran 11 provide prevalence estimates for 1990 and 2016 or 2017, but there are no actual prevalence data for these countries in those years.…”
Section: Introductionmentioning
confidence: 69%
“…We recently reviewed the prevalence reports used in GBD 2017 to gain a better idea of data coverage. 7 We found that there were only prevalence studies for 103 of the 204 countries, making it difficult to study global LBP burden. Judging whether LBP burden is changing over time is also challenging as only sixteen countries had at least one prevalence study for each of the GBD Study time periods 1987–1996, 1997–2006 and 2007–2017.…”
Section: Introductionmentioning
confidence: 95%
“…Internal and external validity of the GBD 2019 LBP disability weights and severity distributions are unknown. Musculoskeletal conditions, and particularly LBP [ 42 ], are less likely than other chronic diseases to have country level data, partly due to their low level of associated mortality. While, modelled estimates aim to adjust for the variable coverage, the heterogeneity of case definitions and the lack of standardisation of data collection, imprecision often exists as seen in the uncertainty in YLDs due to all MSK causes.…”
Section: Limitationsmentioning
confidence: 99%